THE CRIME OF SEXUAL VIOLATION ACCORDING TO SOCIOLOGICAL CRIMINOLOGY IN THE CITY OF PUNO - Xussan Lillian Flores Medina (2020)
At present, the crimes of rape are permanently produced in our city of Puno, due to the consumption of alcoholic substances and lack of ethyl culture; They are both social alarm phenomena, because the media and society focus on them as an element of social problems. According to Sociological Criminology, what are the factors that affect the commission of rape in the city of Puno? In which places in the city are the crimes of rape most committed? What are the numbers of rape in the last two years of 2018 and 2019? Given these questions, this article analyzes this problem of the reality of Puno. The description and analysis will be based on the socio-criminological doctrines, and the statistical data of PUNO POLICE REGION (AREINCRI), CEM that provide figures and information on sexual violations that arise in our city, concluding that in criminal treatment should take in “the social” consideration, study the criminological event taking into account social facts, human interactions, collective events, to go in search of their understanding and understanding of criminal acts, in order to propose preventive policies and reduce the commission of rape sexual.